Fenomena Calo Liar - Syahribulan Syahribulan; Sitti Fatima Tolla; Muh Rizal (Universitas Muhammadiyah Makassar, 2018)
Wild brokers or commonly known as car agents are jobs that offer services to passengers to be transported to a car that aims at the passenger area. The purpose of this study was (i) to know the motivating factors for someone working as a wild broker, especially brokers in the power terminal of the city of Makassar. (ii) This study also aims to determine the impact that is generated by the presence of brokers at the Makassar City Power Terminal. This study used descriptive qualitative method. Target in the research of all brokers inside and outside the terminal, passengers, terminal officers and car drivers. The sample chosen was 4 brokers, 4 terminal officers, 3 passengers and 4 car drivers. Sampling in this study was taken by using interview techniques. The results of the study showed that the difficulties in getting a job, urbanization factors, and economic factors became the basis for someone working as a broker. with the presence of brokers at the Makassar city power terminal it turned out to provide a loss to the passengers, car drivers and terminal officers.Keywords: Brokers, Terminals, Social Deviations.